A study of the iterative type I polyketide synthases in enediyne and mellein biosynthesis - Sun, Huihua (2013)
Iterative type I polyketide synthases (iPKSs) are large multifunctional enzymes that assemble polyketide products by using a single module composed of several catalytic domains. Although iPKSs utilize the same repertoire of catalytic domains as fatty acid synthases and modular PKSs, iPKSs are able to use a single set of catalytic domains to assemble the chemically and structurally diverse polyketide products in an iterative manner. How the iPKSs achieve the chemical and structural diversity by “programming” the catalytic domains remains one of the greatest mysteries in enzymology today. In this thesis, I describe the results from my studies on two iPKSs that aimed to understand the function and mechanism of the multifunctional iPKSs.